2014
DOI: 10.15294/jdm.v5i2.3663
|View full text |Cite
|
Sign up to set email alerts
|

Peran Stres Kerja Dan Kepuasan Kerja Untuk Mengurangi Turnover Intention

Abstract: <p>Tujuan penelitian ini untuk menguji pengaruh variabel stres kerja dan kepuasan kerja pada turnover intention karyawan tetap bagian produksi. Sampel penelitian ini adalah 86 responden, menggunakan metode Slovin dengan teknik probability sampling dengan jenis proportionate random sampling. Berdasarkan hasil penelitian, menunjukkan bahwa stres kerja berpengaruh positif signifikan pada turnover intention. Kemudian, kepuasan kerja berpengaruh negatif signifikan. Penelitian ini menyimpulkan, bahwa stres ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
2
4
0
11
Order By: Relevance
“…This study showed if employees were committed to the organization, they would maintain membership in the organization and would not be looking for another job. This finding was consistent with the attribution theory which stated that the actions of employees doing the turnover intention could be sourced from employees' internal factors that was organizational commitment (Meyer et al, 2002;Salleh et al, 2012;Biantoro & Sihombing, 2012;Jehanzeb et al, 2013;Nazenin & Palupiningdyah, 2014;Saeed et al, 2014;Yasmin & Marzuki, 2015).…”
Section: Regression Analysissupporting
confidence: 85%
“…This study showed if employees were committed to the organization, they would maintain membership in the organization and would not be looking for another job. This finding was consistent with the attribution theory which stated that the actions of employees doing the turnover intention could be sourced from employees' internal factors that was organizational commitment (Meyer et al, 2002;Salleh et al, 2012;Biantoro & Sihombing, 2012;Jehanzeb et al, 2013;Nazenin & Palupiningdyah, 2014;Saeed et al, 2014;Yasmin & Marzuki, 2015).…”
Section: Regression Analysissupporting
confidence: 85%
“…Penelitian Nazenin dan Palupiningdyah (2014) menyatakan bahwa kepuasan kerja berpengaruh negatif dan signifikan terhadap turnover intention karyawan tetap bagian produksi. Hal ini berarti semakin rendah kepuasan kerja karyawan maka akan meningkatkan turnover intention karyawan, sebaliknya semakin tinggi kepuasan kerja karyawan maka akan menurunkan turnover intention karyawan (Nazenin & Palupiningdyah, 2014).…”
Section: Hubungan Kepuasan Kerja Dan Turnover Intentionunclassified
“…Human resources are a challenge for management, because the success of management and others depends on the quality of human resources (Ranihusna, 2010). Human resources in this case the employees are required to have a work spirit, so as to provide maximum performance for the company (Nazenin & Palupiningdyah, 2014). Human Resources (HR) that are superior with high quality are the demands of every organization to be able to achieve the goals set (Sudarma, 2012).…”
Section: Introductionmentioning
confidence: 99%